Identification and phylogenetic analysis of Jingmen tick virus in Jiangxi Province, China - Liu, Zirui; Hu, Ruiming; Cao, Huabin; Huang, Peng; Yan, Hui; Meng, Puyan; Xiong, Zhiwei; Dai, Xueyan; Yang, Fan; Wang, Li; Qiu, Qian; Yan, Linjie; et al. (Frontiers in Veterinary Science, 2024)
Jingmen tick virus (JMTV) is a newly identified segmented flavivirus that has been recognized in multiple hosts, such as humans, buffalos, bats, rodents, mosquitos and ticks. Various clinical cases and studies manifested that JMTV is a true arbovirus with wide host spectrum and showed potential threats toward public health. JMTV has been reported in multiple countries in Asia, Europe, Africa, and America. Moreover, wild boars serve as an important intermediary between humans and the wild ecological system. In China, it has been reported in nine provinces, while the prevalence and the distribution of JMTV in most regions including Jiangxi Province are still unknown. Thus, to profile the distribution of JMTV in Jiangxi Province, an epidemiological investigation was carried out from 2020 to 2022. In current study, 66 ticks were collected from 17 wild boars in Jiangxi Province. The results showed that 12 out of 66 ticks were JMTV positive, indicating JMTV is prevalent in ticks and boars in Jiangxi Province. The genome sequences of JMTV strain WY01 were sequenced to profile viral evolution of JMTV in China. Phylogenetic analysis divided JMTV strains into two genotypes, Group I and Group II. WY01 belongs to Group II and it shares the closest evolutionary relationship with the Japan strains rather than the strains from neighboring provinces in China suggesting that JMTV might have complex transmission routes. Overall, current study, for the first time, reported that JMTV is prevalent in Jiangxi Province and provided additional information concerning JMTV distribution and evolution in China.